2018
DOI: 10.31820/pt.27.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Can Psychopathic Traits be Adaptive?

Abstract: One of the most prominent models of psychopathy operationalizes this construct as consisting of four factors: interpersonal, affective, lifestyle and antisocial traits. These traits show different relationship patterns with other constructs, and these relations may differ in men and women. The aim of this study was to investigate whether the relations between psychopathic traits and indicators of emotional distress (depression, anxiety and stress), differ between men and women. Data was collected on 650 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The results showing that psychopathic traits were not a moderator between trauma and recidivism support the results of Međedović et al (2018) who found that psychopathic traits are less adaptive for females than males. The hypothesis examined in this study, -that psychopathic traits operate as a moderating resilience factor for women who have experienced trauma in the reentry process, was not supported.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results showing that psychopathic traits were not a moderator between trauma and recidivism support the results of Međedović et al (2018) who found that psychopathic traits are less adaptive for females than males. The hypothesis examined in this study, -that psychopathic traits operate as a moderating resilience factor for women who have experienced trauma in the reentry process, was not supported.…”
Section: Discussionsupporting
confidence: 83%
“…For example, traits such as fearlessness, disinhibition, and narcissism are associated with heroic behaviors (Bronchain et al, 2020a(Bronchain et al, , 2020b. Međedović et al (2018) found that some psychopathic traits have an adaptive potential and are a protective factor that moderates emotional distress.…”
Section: Psychopathic Traits Trauma and Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…The scores for the ASB subscale were much lower compared with the other subscale of the SRP, which is consistent with the findings obtained by Gordts, Uzieblo, Neumann, Van den Bussche, and Rossi (2017). Compared with the scores obtained in a large Belgian community sample (Gordts et al, 2017), in an American community sample (Paulhus et al, 2017), and in another Croatian sample (Međedović, Wertag, & Sokić, 2018), internal consistency coefficients and other descriptive statistics of the SRP and its subscales in the current sample were very similar. It is worth noting that, in the current study, the values of skewness and kurtosis indicated normal distributions of the scores in the full version of the SRP and all the subscales, except for the Antisocial behaviour scale, which was skewed towards the lower scores.…”
Section: Reliabilities and The Descriptive Statistics Of The Analysedsupporting
confidence: 89%
“…As women are more likely to express emotions than men [83] and men are more likely to experience difficulty in emotional regulation than women [84,85], girls experience more intense negative emotions than boys when their self-harmony level is reduced during adolescence. Me dedovi'c et al also found that the emotional and interpersonal aspects of mental illness predicted greater emotional distress in women than in men [86]. Whalen et al demonstrated that the prevalence of depression in girls is higher than that in boys [87].…”
Section: Analysis Of the Moderating Effect Of Gendermentioning
confidence: 98%